Effects of grazing system and stocking rate on cow-calf performance in the flint hills - Cochran, R.C.; Johnson, D.E.; Olson, K. C.; Hartnett, David C.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 6-year study was designed to measure the influences of stocking rate and grazing system on performance of cow-calf pairs grazing tallgrass prairie. This paper summarizes the initial 3 years. Late-season rest-rotation was compared to continuous grazing over low, moderate, and high stocking rates. No differences (P>.10) were observed in body weight of cows or calves as a result of grazing system or stocking rate. However, calf weaning weight tended (P=.20) to be greater with continuous grazing than with late season rest-rotation. Cow body condition score was unaffected (P>.10) by stocking rate or grazing system. Conception rates were also similar between stocking rates and grazing systems. This preliminary information suggests that application of a late-season rest-rotation grazing system will support cow-calf performance comparable t o that with a continuous system at a similar stocking rate.
Keywords: Beef; Stocking rate; Grazing systems; Cow-calf performance